2016
DOI: 10.1159/000443895
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Treatment Serum C-Reactive Protein Level Is An Independent Risk Factor for Development of Nephrotoxicity in Patients Receiving High-Dose Vancomycin

Abstract: High-dose vancomycin treatment increases the likelihood of vancomycin-related nephrotoxicity. C-reactive protein (CRP) is a sensitive marker of systemic inflammation. In this study, we evaluated the pre-treatment serum CRP level as a risk factor of the development of nephrotoxicity in patients receiving high total daily doses (>2.5 g) of vancomycin. Data extracted from medical records for 174 patients who received total daily doses of >2.5 g of intravenous vancomycin for a minimum of 48 h and had their serum C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Among these, 261 studies were excluded for the following reasons: evaluating antibiotics other than vancomycin ( n = 104), evaluating outcomes other than AKI ( n = 45), not assessing risk factors ( n = 68), not original articles ( n = 4), involving paediatric patients ( n = 8), involving nonhuman subjects ( n = 12), overlapping study population ( n = 3), not a patient‐level analysis ( n = 1), involving patients who underwent renal replacement therapy ( n = 4), and data extraction not possible or feasible ( n = 12). Finally, 53 studies were included in the meta‐analysis 6–8,10–12,21–67 . A flow diagram summarizing the study selection process is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Among these, 261 studies were excluded for the following reasons: evaluating antibiotics other than vancomycin ( n = 104), evaluating outcomes other than AKI ( n = 45), not assessing risk factors ( n = 68), not original articles ( n = 4), involving paediatric patients ( n = 8), involving nonhuman subjects ( n = 12), overlapping study population ( n = 3), not a patient‐level analysis ( n = 1), involving patients who underwent renal replacement therapy ( n = 4), and data extraction not possible or feasible ( n = 12). Finally, 53 studies were included in the meta‐analysis 6–8,10–12,21–67 . A flow diagram summarizing the study selection process is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Forty-eight studies 9,18–22,25,26,31–34 with 36–61 scores 63–67 of 69–73 ≥7 on the Newcastle–Ottawa scale were considered for the meta-analysis. Of these, 10 included patients aged <18 years (neonates–adolescents).…”
Section: Resultsmentioning
confidence: 99%
“…Among the 57 included studies (Table 2), 4 made direct comparisons between AUC-guided and trough-guided cohorts 9,18–20 ; 10 reported both AUC-guided and trough-guided monitoring 21–28,64,65 ; 2 reported only AUC-guided monitoring 29,30 ; and 41 reported only trough-guided monitoring. 31–63,66–73 Four studies had vancomycin doses adjusted based on both AUC-guided and trough-guided monitoring; 48 had vancomycin doses adjusted based solely on trough-guided monitoring; and 5 had vancomycin doses titrated based solely on AUC-guided monitoring. Most studies were from the United States (n = 34) and Asia-Pacific region (n = 18).…”
Section: Resultsmentioning
confidence: 99%
“…Degenerative changes in renal glomeruli and tubules were also reported in the gentamicin-treated group. Med J 20:2 (2019) 20-27 The nephrotoxic effect of gentamicin administration was clearly described in many previous studies, manifested by elevation of serum BUN and creatinine levels (Lopez-Novoa et al, 2011;Boroushaki and Sadeghnia, 2015;Balakumar et al, 2017;, elevation of serum inflammation marker (CRP) (Balakumar et al, 2010;El-Ashker et al, 2015;and He et al, 2016), and alteration in oxidative/antioxidative status biomarkers in form of increased MDA and decreased superoxide dismutase (SOD), glutathione (GSH), and catalase (CAT) activities (Abdel-Raheem et al, 2009;Patil et al, 2014;and Casanova et al, 2017). The histopathological alterations reported in this study are consistent with the former studies.…”
Section: Discussionmentioning
confidence: 95%